Malignant Leiomyoblastoma: An Incidental Diagnosis - Ray, S; Basak, S; Chatterjee, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11147 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 55-56